Standardization of platelet parameters determination in blood samples collected with EDTA - Silveira, M. M. [UNESP]; Fonseca, Luiz Marcos da [UNESP] (My University, 2003)
The Abbott Cell-Dyn 3000 automated hematological analyzer prepares a histogram of platelet volume, which is measured by a technique using electrical impedance, inferring from its platelet count (PLT), mean platelet volume (MPV) and platelet distribution width (PDW). This equipment also calculates the plateletcrit (PCT). These platelet parameters may be important to evaluate platelet function, but they require standardization, because platelets swell when in contact with ethylenediaminetetra-acetic acid salts, hence an increase in blood sample storage time produces artificially increased results. To assess the effect of storage time on MPV, PLT, PDW and PCT, blood samples from 23 sickle cell anemia patients during steady state (Group I) and 50 from healthy controls (Group II) were placed in Vacutainer® tubes with dipotassium ethylenediaminetetra-acetic acid and measured over a period of 1440 minutes (24 h) at the following times: immediately after the venipuncture (time 0), 15, 30, 60, 120, 240, 360, 480 and 1440 minutes. The mean values of MPV and PCT were significantly increased (p<0.00001) along the storage time in both groups. The mean values of PLT and PDW were practically stable (p>0.05) throughout the storage time in both groups.
Keywords: Blood sample storage time; Ethylenediaminetetra- acetic acid; Mean platelet volume; Plateletcrit; Standardization; blood analysis; blood sampling; blood storage; cell swelling; controlled study; diagnostic value; histogram; human; human cell; impedance; mean platelet volume; platelet distribution width; sickle cell anemia; standardization; storage time; thrombocyte; thrombocyte count; thrombocyte preservation; thrombocyte volume; time; vein puncture